Features of Cadences in Vocal and Choral Music of the Seventeenth Century (on the Example of Giovanni Palestrina’s Motets) - Gomeniuk, Svitlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the study. The traditional idea of a cadence as a primarily harmonic phenomenon does not completely correspond to some musical styles, including Renaissance and early Baroque. Revealing the polyphonic essence of cadences in vocal works of the Renaissance, which is the aim of the article, allows deeper understanding peculiarities of musical thinking of that period. Scientific novelty. The historical approach to the analysis of cadences is quite common in foreign musicological works; this approach is still new for Ukrainian musicology. The research material is also new: the cycle of motets by G. Palestrina on the text of “Song of Songs” was unfairly ignored by Ukrainian and foreign scholars. Thus, the study is relevant both in relation to the method and in relation to the musical material involved in its approbation. The purpose of the article is to show the specifics of cadences in the style of a strict counterpoint using the motets from the cycle “Canticum Canticorum” by G. Palestrina, to reveal the role of cadences in the modal and compositional processes of a Renaissance work. Research methods. The study systematizes the data obtained as a result of the analysis of the cadences of G. Palestrina’s motets, thus, the main research method is inductive. The main results and conclusions of the study. Cadences in vocal polyphony of the Renaissance have a polymelodic nature, which is realized by combining typical melodic turns (clausulae) in different voices. The clausulae order in the voices and their completeness degree are effective criteria for the classification of cadences (e. g. the classification by E. Rotem). Cadences in which the main clausulae are presented in full (i. e. contain ultima and penultima) are strong. Cadences in which one or more clausulae are incomplete are weak. The role of strong and weak cadences in the composition is different: strong cadences are placed at the nodal points of the piece, they have a dividing function; weak cadences are placed in the middle of the text line and they have a connecting function. Strong cadences are the norm, while weak ones violate the norm, revealing the author’s ingenuity. There are a few ways to weaken the cadence: replacing the ultima with a pause or a different sound, distributing the clausula between several voices, extending the melodic line of one of the cadence voices, etc. Weak cadences significantly outnumber strong cadences. In the Dorian motets from the cycle “Song of Songs” by G. Palestrina weak cadences play an important role in the formation of the mode within the sound scale, as well as in revealing the meaning of the verbal text.